Operations management : sustainability and supply chain management. - Heizer, Jay; Render, Barry; Munson, Chuck (Charles Lee) (Pearson, 2023)
This textbook provides students with a state-of-the-art overview of operations management. It is aimed at the introductory operations management course, at both the undergraduate and graduate level.